1999
DOI: 10.1034/j.1600-051x.1999.260501.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary lactoferrin and low‐Mr mucin MG2 in Actinobacillus actinomycetemcomitans‐associated periodontitis

Abstract: Concentrations and output of lactoferrin and of low-Mr mucin MG2 were determined in saliva of subjects suffering from Actinobacillus actinomycetemcomitans-associated periodontal disease and healthy subjects. Periodontal patients were clinically examined and a microbiological sample was taken from the deepest bleeding pockets in each quadrant. The number of viable A. actinomycetemcomitans was determined in the sampled sites of each patient. The MG2 output in the diseased subjects (13.6 microg protein/min) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 27 publications
5
67
2
1
Order By: Relevance
“…Our study is in accordance with the study done by Groenink et al, [33] who showed that MG2 output was decreased in individuals with aggressive periodontitis in comparison with periodontal healthy subjects.…”
Section: Discussionsupporting
confidence: 83%
“…Our study is in accordance with the study done by Groenink et al, [33] who showed that MG2 output was decreased in individuals with aggressive periodontitis in comparison with periodontal healthy subjects.…”
Section: Discussionsupporting
confidence: 83%
“…Lactoferrin is upregulated in the salivary secretions in gingival inflammation and periodontal diseases as compared to normal healthy individuals. It also bears a correlation with the A. actinomycetemcomitans species [16]. Histatin is another salivary protein with antimicrobial properties which neutralizes the endotoxic lipopolysaccharides located on Gramnegative bacteria.…”
Section: Salivary Biomarkersmentioning
confidence: 99%
“…(4,(10)(11)(12) and antimicrobial proteins and peptides. These include lysozyme (13,14), lactoferrin (15,16), acidic proline-rich proteins (17,18), plunc (19,20), salivary mucin glycoprotein (16,21), histatin (13,17,22), defensin HBD1 (23,24), defensin HBD2 (25)(26)(27), defensin HBD3 (26,27), defensin HBD4 (26,27), and hCAP18/LL-37 (28). Fatty acids and long-chain bases found at the skin surface have strong bactericidal activity (29)(30)(31)(32)(33).…”
Section: Innate Immune Mechanismsmentioning
confidence: 99%